Effect of Endometrial Thickness Change in Response to Progesterone Administration on Pregnancy Outcomes in Frozen-Thawed Embryo Transfer: Analysis of 4465 Cycles - Ye, Jing; Zhang, Jie; Gao, Hongyuan; Zhu, Yanwen; Wang, Yao; Cai, Renfei; Kuang, Yanping (Frontiers in Endocrinology, 2020)
Objective To evaluate whether endometrial thickness (EMT) change in response to progesterone has an effect on pregnancy outcomes in frozen-thawed embryo transfer (FET) cycles. Design Retrospective observational study. Setting Tertiary-care academic medical center. Participants 4465 infertile women undergoing their first FET between January 2010 and December 2015 in our center. Methods This observational study included 4465 patients undergoing their first FET cycles between January 2010 and December 2015. EMT was measured by transvaginal ultrasound one day before progesterone administration and on the day of FET to observe EMT change. Main outcome measures Clinical pregnancy rate (CPR) and the live birthrate (LBR) was discussed. Results Regardless of the endometrial preparation protocols such as artificial cycle, estrogen-progesterone replacement therapy (EP) or natural cycle (NC), EMT may increase, decrease or remain stable on the day of FET compared with that one day before progesterone administration. CPR in EMT increase, decrease and stable groups was 48.4%, 51.3% and 50.7% in EP cycle versus 49.2%, 52.0% and 48.9% in NC cycle, showing no significant difference between the three groups in both cycles (P= 0.48, P= 0.49). LBR was 40.9%, 45.9% and 42.6% in EP cycle versus 44.2%, 44.8% and 42.1% in NC cycle, neither showing significant difference between the three groups in both cycles (P= 0.16, P= 0.66, P). In addition, CPR and LBR were not significantly associated with EMT increase. Concludes: EMT may increase, decrease or remain stable on the day of FET as compared with that one day before progesterone administration. Whatever change in EMT that occurs after progesterone administration has no significant effect on CPR and LBR in FET cycles.